2010
DOI: 10.1007/s12094-010-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and myocardial metastases of a primary pulmonary melanotic schwannoma

Abstract: We present the case of a 60-year-old man with a primary pulmonary melanotic schwannoma treated with surgery and who developed an orbital and myocardial relapse 2 years after the initial diagnosis. Melanotic schwannomas are rare pigmented tumours that tend to arise from the peripheral nerves near the midline. A primary lung presentation, as in our case, is extremely rare. In more than half of cases, the Carney triad of myxomas of the heart, skin and breast, spotty pigmentation and endocrine hyperactivity is pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In our literature review we only found 17 articles describing 18 cases of intracranial MS (►Table 1). 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Mean age at presentation was 36.3 years (range: 11-77 years), with a strong male predominance (male-to-female ratio: 13:3). MSs mainly occur sporadically, but less frequently they may present as a manifestation of NF II or CC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our literature review we only found 17 articles describing 18 cases of intracranial MS (►Table 1). 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Mean age at presentation was 36.3 years (range: 11-77 years), with a strong male predominance (male-to-female ratio: 13:3). MSs mainly occur sporadically, but less frequently they may present as a manifestation of NF II or CC.…”
Section: Resultsmentioning
confidence: 99%
“…1,5,6,9,17,25,30,53,58,[60][61][62] Radiation therapy may or may not be associated with chemotherapy. 1,8,20,25,36,63 Vallat-Decouvelaere and Zhang observed a lower rate of recurrence and metastasis in patients treated with radiotherapy as adjuvant treatment, suggesting its positive role in the treatment of MS. 1,25 Because of the potential aggressive behavior and the long time to progression, a patient harboring intracranial MS should strictly follow up, even in the case of GTR. 1,4,6,8,9,20,[32][33][34]36,45,54 In the study of Lowman and Livolsi of two spinal MSs, disease control in the case of STR plus radiotherapy was 14 years compared with 17 years in the case of GTR only.…”
Section: Immunohistochemistrymentioning
confidence: 98%
See 2 more Smart Citations